2006
DOI: 10.1182/blood-2006-02-003954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic graft-versus-host disease on the health status of hematopoietic cell transplantation survivors: a report from the Bone Marrow Transplant Survivor Study

Abstract: The aim of this study was to understand the impact of chronic graft-versus-host disease (cGVHD) on the overall health status of hematopoietic cell transplantation (HCT) survivors. Subjects included 584 individuals who had undergone allogeneic HCT between 1976 and 1999, survived 2 or more years, and completed a 255-item health questionnaire. Global assessment of health status was facilitated by measurement of 6 health status domains: general health, mental health, functional impairment, activity limitation, pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
199
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(209 citation statements)
references
References 28 publications
7
199
2
1
Order By: Relevance
“…[17][18][19][20][21][22] To date, very few studies have investigated the impact of ECP on QoL. In the only randomized controlled trial to date, Flowers et al 10 used a Targeted Symptoms Assessment questionnaire, which included 12 questions to assess the effect of cutaneous, ocular and oral GVHD on various aspects of patients' QoL.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] To date, very few studies have investigated the impact of ECP on QoL. In the only randomized controlled trial to date, Flowers et al 10 used a Targeted Symptoms Assessment questionnaire, which included 12 questions to assess the effect of cutaneous, ocular and oral GVHD on various aspects of patients' QoL.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,10,12,13,20 Several scholars indicated that use of mismatched or unrelated donors was a risk factor for cGVHD. 20 However, Teshima et al 21 only noted a tendency for increasing cGVHD with increasing HLA disparity, rather than a statistically significant correlation (P ¼ 0.05); other studies found that the occurrence of cGVHD did not differ between patients receiving ISD vs HID/PMRD HSCT, 22,23 which may be due to the usage of ATG in these studies.…”
Section: Sf-36 Scoresmentioning
confidence: 99%
“…[15][16][17] We assigned a value of 100 to the utility for being alive without relapse at 10 years after chemotherapy alone, and a value of 0 to the utility for being dead in all situations. We assigned a fixed value of 98 to the utility for being alive without active GVHD at 10 years following HSCT, and assigned a value of 70 with a wide plausible range of 0-98 to the utility for being alive with active GVHD at 10 years.…”
Section: Transition Probabilities (Tps) and Utilitiesmentioning
confidence: 99%